Mortality from asthma in the state of S. Paulo, Brazil (1970-1992) - Lotufo, Paulo Andrade (1995)
Mortality from asthma has shown important variations over time in several countries. In Brazil, a mortality study performed in the 60s, covering the cities of S.Paulo and Ribeirão Preto, and other ten cities showed that S.Paulo presented the lowest death rate from asthma among of them all. It was decided to study the time trends of deaths from asthma and from the whole set of respiratory diseases from 1970 to 1992, in the population aged 15-34 yrs. old in the State of S.Paulo, as well as to compare them with those of other countries. Asthma mortality rates during the 23 years of observation since 1975, showed an oscillatory declining pattern with a peak of deaths in the initial years. The linearization of the curve allows the calculation of Pearson's correlation coefficient that was significantly negative, suggesting a decline in the mortality over this period, mainly in the 5-9 yrs. old and 30-34 yrs. old strata. The segmentation of data between the period of ICD-9, 1970 to 1978, and of ICD-9, 1979 and subsequent years, shows that there is stability within each period, in all age-groups, except for that of 5-9 yr. olds between 1970-1978. Comparing the rates of the population aged 15-34 yrs. old for the State of S. Paulo, Brazil, with trends observed in 14 other countries, an intermediate pattern for the first triennial period (1970-1972) as well as for the subsequent triennial periods, emerges. A prevalence study of asthma, a follow up program meant for using emergency rooms and a surveillance of deaths due to all respiratory diseases and specifically to asthma are strongly recommended.